2022
DOI: 10.1002/tox.23589
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic STAMP2 alleviates polychlorinated biphenyl‐induced steatosis and hepatic iron overload in NAFLD models

Abstract: Polychlorinated biphenyls (PCBs) have been associated with neurotoxicity, hepatoxicity, oncogenicity, and endocrine-disrupting effects. Although the recent studies have demonstrated that PCB exposure leads to nonalcoholic fatty liver disease (NAFLD), the underlying mechanism has remained unsolved. In this study, we examined the hepatic effects of a PCB mixture, Aroclor 1260, whose composition mimics human bioaccumulation patterns, and PCB 126 in C57BL/6 mice. Male C57Bl/6 mice were fed a standard diet or a 60%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…However, to our knowledge, our study is the first to reveal an interaction between SLC40A1 and Steap4, which facilitated SLC40A1-mediated iron efflux. It has been documented that Steap4, unlike Steap3 which promotes iron uptake 38 , promotes intracellular iron excretion 39 , 40 . These results support our findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge, our study is the first to reveal an interaction between SLC40A1 and Steap4, which facilitated SLC40A1-mediated iron efflux. It has been documented that Steap4, unlike Steap3 which promotes iron uptake 38 , promotes intracellular iron excretion 39 , 40 . These results support our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that hepatic STAMP2 mediates recombinant FGF21-induced improvements in hepatic iron overload in nonalcoholic fatty liver disease through the upregulation of expression of the iron exporter, ferroportin [ 26 ]. In addition, we have also shown that hepatic STAMP2 alleviates polychlorinated biphenyl (PCB)-induced steatosis in NAFLD in in vivo and in vitro models [ 28 ]. These studies support that STAMP2 targeting could be a potential strategy for NAFLD accompanying HIO.…”
Section: Stamp2 Is a Hepatic-iron-overload-targeted Modulator Of Nafldmentioning
confidence: 99%
“…We previously showed that hepatic STAMP2 plays a pivotal role in alleviating either high-fat-diet (HFD)- or environmental-pollutant (polychlorinated biphenyl, PCB)-induced NAFLD and upregulation of STAMP2 using adenoviral STAMP2 ameliorates hepatic steatosis, inflammation, and iron overload in NAFLD, in in vivo and in vitro models [ 24 , 25 , 26 , 27 , 28 ]. Structurally, STAMP2 has metalloreductase activity and functions in iron and copper homeostasis [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Significant amounts of BFRs have spread throughout the world, even to West Africa [6] and the polar regions [29]. Several epidemiological reports have demonstrated the presence of these organic compounds in humans and wildlife [22,35,39] emphasizing their ability to accumulate in many tissues [16,19,38,42]. Both groups of compounds are character-ized by a high degree of lipophilicity, which allow them to preferentially accumulate in lipid-rich regions of the body such as adipose tissue and the brain.…”
Section: Introductionmentioning
confidence: 99%
“…It has been postulated that inflammatory processes may be involved in the toxicant-induced pathology in peripheral tissues. PCBs have been shown to activate a pro-inflammatory signalling cascade associated with atherosclerosis [4] and hepatic disorders [19], and participate in the development of inflammatory diseases [25]. 2,2',4,4',5,5'-heksachlorobiphenyl (PCB 153) has been shown to up-regulate the inflammatory enzyme cyclooxygenase-2 (COX-2) and the proinflammatory cytokines in human mast cells [20].…”
Section: Introductionmentioning
confidence: 99%